JIM REAPER : Saving Granny Maggot - Delahaye, Rachel; Littler, Jamie (London : Piccadilly Press, 2016)
Book 2 in a hilarious series about a boy who discovers his dad is keeping a huge secret. What would you do if you discover your dad might be death? Another fast, fun and fearless adventure about life, death and all the hilarity in between.
Keywords: Grim Reaper (Symbolic character) -- Juvenile fiction; families -- Juvenile fiction; Children's stories